2009
DOI: 10.1186/1742-4755-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Limits to modern contraceptive use among young women in developing countries: a systematic review of qualitative research

Abstract: Increasing modern contraceptive method use requires community-wide, multifaceted interventions and the combined provision of information, life skills, support and access to youth-friendly services. Interventions should aim to counter negative perceptions of modern contraceptive methods and the dual role of condoms for contraception and STI prevention should be exploited, despite the challenges involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
295
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(323 citation statements)
references
References 58 publications
22
295
1
5
Order By: Relevance
“…2013; Williamson et al. 2009; Castle 2003). Such concerns are likely to be more of a deterrent to use and selection of methods among younger women wishing to space or postpone childbearing than among those wanting to limit family size.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Williamson et al. 2009; Castle 2003). Such concerns are likely to be more of a deterrent to use and selection of methods among younger women wishing to space or postpone childbearing than among those wanting to limit family size.…”
Section: Discussionmentioning
confidence: 99%
“…These findings compare with those reported elsewhere. Williamson et al [18] conducted a synthesis of several studies from developing countries, many of which reported inaccurate perceptions of pregnancy risk among young women, limited understanding of modern contraceptives and general misconceptions about how to use them properly.…”
Section: Discussionmentioning
confidence: 99%
“…These difficulties are compounded by problems of access: in common with many other developing countries, unmarried adolescents in Sri Lanka face considerable difficulties accessing family planning or reproductive health services because they are only available to, or perceived to be only available to those who are married. [4,18] The literature identifies substantial areas of concern and suggests that Sri Lankan adolescents are ill equipped to make informed decisions about sexual activity and protect themselves from the unwanted consequences. However, ten years have elapsed since the UNICEF study and further work is indicated to determine the extent to which progress has been made.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a review of limits to use of modern contraceptives in developing countries, the authors present a matrix that lists the 10 emerging themes against the seven included studies, noting which studies attempted to address which theme (Williamson et al 2009). The approach taken by Munro et al (2007) in their meta-ethnographic review of patients' adherence to tuberculosis treatment is to present primary themes (views and understandings of participants) and secondary themes (interpretations by authors of primary studies), although references to the articles which reported this are not made, and it is not immediately obvious which themes supersede or have greater weighting than others.…”
Section: Options For Synthesis Of Qualitative and Mixed Methods Evidencementioning
confidence: 99%
“…Existing reviews of qualitative evidence have adopted different approaches. Some authors have assessed the quality of included studies using existing quality appraisal tools and excluded studies judged to be of low quality from the synthesis (Campbell et al 2003, Pound et al 2005, Williamson et al 2009), while others have opted to systematically assess study quality, without excluding studies on the basis of quality (Thomas et al 2003, Munro et al 2007. In a review of the barriers and facilitators to children's healthy eating, the authors conducted a sensitivity analysis and found that including the weaker studies did not affect the results of their synthesis (Thomas et al 2003), leading them to conclude they will exclude studies of lower quality in the future (Thomas et al 2004).…”
Section: Controversies Around Quality Appraisalmentioning
confidence: 99%